"Public tertiary education expenditure in Portugal: a non-parametric efficiency analysis - Afonso, António (2004)
We employ a non-parametric methodology, Data Envelopment Analysis, to estimate efficiency scores for Portuguese public universities for 2001. Due to the tertiary education organisational features we consider universities as well as faculties and institutes as decision entities. Using frontier analysis we are able to separate universities/faculties/institutes that might qualify, as "performing well" from those were some improvement might increase its efficiency. This is a first effort of checking efficiency and productivity in Portuguese public tertiary education using non-parametric analysis.